(untitled) - Wilson, Jerry R. (Malaysia, 2008)
This book demonstrates that business owners don’t have to constantly replace employees or use artificial incentives and harsh methods to get employees to help the business succeed. Wilson shows business owners and managers how to do it themselves without the pain and suffering. And you don’t have to invent any new approaches, concepts, or buzzwords to do it! Just follow some of Jerry Wilson’s 151 proven ideas and discover amazing results…fast!
Keywords: Employee motivation,Phát triển người lao động